A patient with a novel homozygous missense mutation in FTO and concomitant nonsense mutation in CETP. - Çağlayan, Ahmet O; Tuysuz, Beyhan; Coşkun, Süleyman; Quon, Jennifer; Harmancı, Akdes S; Baranoski, Jacob F; Baran, Burçin; Erson-Omay, E Zeynep; Henegariu, Octavian; Mane, Shrikant M; Bilguvar, Kaya; Yasuno, Katsuhito; et al. (J Hum Genet, 2016)
The fat mass and obesity associated (FTO) gene has previously been associated with a variety of diseases and conditions, notably obesity, acute coronary syndrome and metabolic syndrome. Reports describing mutations in FTO as well as in FTO animal models have further demonstrated a role for FTO in the development of the brain and other organs. Here, we describe a patient born of consanguineous union who presented with microcephaly, developmental delay, behavioral abnormalities, dysmorphic facial features, hypotonia and other various phenotypic abnormalities. Whole-exome sequencing revealed a novel homozygous missense mutation in FTO and a nonsense mutation in the cholesteryl ester transfer protein (CETP). Exome copy number variation analysis revealed no disease-causing large duplications or deletions within coding regions. Patient's, her parents' and non-related control' fibroblasts were analyzed for morphologic defects, abnormal proliferation, apoptosis and transcriptome profile. We have shown that FTO is located in the nucleus of cells from each tested sample. Western blot analysis demonstrated no changes in patient FTO. Quantitative (qPCR) analysis revealed slightly decreased levels of FTO expression in patient cells compared with controls. No morphological or proliferation differences between the patient and control fibroblasts were observed. There is still much to be learned about the molecular mechanisms by which mutations in FTO contribute to such severe phenotypes.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Apoptosis; Biopsy; Child, Preschool; Cholesterol Ester Transfer Proteins; Computational Biology; Consanguinity; DNA Copy Number Variations; DNA Mutational Analysis; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Association Studies; Genotype; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Mutation, Missense; Phenotype; Transcriptome

Mutations in KATNB1 cause complex cerebral malformations by disrupting asymmetrically dividing neural progenitors. - Mishra-Gorur, Ketu; Çağlayan, Ahmet Okay; Schaffer, Ashleigh E; Chabu, Chiswili; Henegariu, Octavian; Vonhoff, Fernando; Akgümüş, Gözde Tuğce; Nishimura, Sayoko; Han, Wenqi; Tu, Shu; Baran, Burçin; Gümüş, Hakan; et al. (Neuron, 2014)
Exome sequencing analysis of over 2,000 children with complex malformations of cortical development identified five independent (four homozygous and one compound heterozygous) deleterious mutations in KATNB1, encoding the regulatory subunit of the microtubule-severing enzyme Katanin. Mitotic spindle formation is defective in patient-derived fibroblasts, a consequence of disrupted interactions of mutant KATNB1 with KATNA1, the catalytic subunit of Katanin, and other microtubule-associated proteins. Loss of KATNB1 orthologs in zebrafish (katnb1) and flies (kat80) results in microcephaly, recapitulating the human phenotype. In the developing Drosophila optic lobe, kat80 loss specifically affects the asymmetrically dividing neuroblasts, which display supernumerary centrosomes and spindle abnormalities during mitosis, leading to cell cycle progression delays and reduced cell numbers. Furthermore, kat80 depletion results in dendritic arborization defects in sensory and motor neurons, affecting neural architecture. Taken together, we provide insight into the mechanisms by which KATNB1 mutations cause human cerebral cortical malformations, demonstrating its fundamental role during brain development.
Keywords: Adenosine Triphosphatases; Animals; Brain; Cell Count; Cell Division; Dendrites; Drosophila; Drosophila Proteins; Humans; Katanin; Mice; Microcephaly; Microtubule-Associated Proteins; Mutation; Neural Stem Cells; Neurogenesis; Optic Lobe, Nonmammalian; Spindle Apparatus; Zebrafish